Interface-based tuning of Rashba spin-orbit interaction in asymmetric oxide heterostructures with 3d electrons - Weinan Lin (Nature Portfolio, 2019)
The two-dimensional electron gases that form at LaAlO3/SrTiO3 heterostructure interfaces feature strong spin-orbit interactions, leading to proposed spintronic applications. Lin et al. show that the design of asymmetric heterostructures enables the Rashba spin-orbit interaction to be tuned between two regimes.